(untitled) (Contextos: Estudios de Humanidades y Ciencias Sociales, 2019)
Analyzing the language of a people also involves reviewing social and human aspects related to the economy. If we want to reliably reveal the synchronic behavior of a certain language of a people, we must analyze its idiosyncrasy, its history and its economy. Consequently, a relevant question when analyzing the language of a society, is to take into account the macro aspects of the economy and its impact on individuals. Here we analyze how the Chilean economy influences the lexical heritage of its inhabitants and the people who have adopted Chile to inhabit.